A rare earth permanent magnetic material with high temperature stability and preparation method thereof

A rare earth permanent magnet with optimized composition and microstructure, using high-abundance element Y, addresses the thermal stability issues of NdFeB magnets, achieving enhanced temperature stability and magnetic properties at a lower cost.

CN118888239BActive Publication Date: 2024-12-27NINGBO KETIAN MAGNET CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411393145.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2024-12-27
Estimated Expiration
2044-10-08

AI Technical Summary

Technical Problem

NdFeB permanent magnets exhibit poor thermal stability due to low Curie temperature and high temperature coefficient, limiting their application at high temperatures, and existing methods to improve temperature resistance either damage magnetic properties or increase production costs.

Method used

A rare earth permanent magnet material with a specific chemical composition and microstructure, including a main phase and grain boundary phase, optimized with high-abundance element Y, combined with a preparation method involving vacuum melting, hydrogen treatment, and two-stage aging heat treatment, to enhance temperature stability and magnetic properties.

Benefits of technology

The magnet achieves improved temperature stability with remanence and coercivity temperature coefficients of 0.06-0.1%/K and 0.4-0.6%/K, respectively, while maintaining good magnetic properties and allowing for low-cost, large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118888239B_ABST
    Figure CN118888239B_ABST
Patent Text Reader

Abstract

The present invention relates to a rare earth permanent magnetic material with high temperature stability and a preparation method thereof. The rare earth permanent magnetic material with high temperature stability comprises the following chemical components by weight percentage: x Y y T z Tm a B b , wherein RE is at least one rare earth element selected from La, Ce, Pr, Nd, Gd, Tb, Dy, Ho, x is 26-30, Y is yttrium, y is 0.5-5, and x+y is 29.8-34; Tm is at least one element selected from Al, Cu, Ga, Zr, Ti, Si, a is 0.5-3; B is boron, b is 0.85-1.1; T is a combination of Fe and Co, z=100-x-y-a-b, and z contains 1-10 parts of Co; the microstructure of the high temperature stability rare earth permanent magnet material includes a main phase and a grain boundary phase, the grain size of the main phase is 2-8 μm, and the concentration of Y in the main phase presents a distribution of high grain center and low grain boundary. The obtained magnet has high temperature stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of rare earth permanent magnetic materials, and in particular to a rare earth permanent magnetic material with high temperature stability and a preparation method thereof. Background Art

[0002] NdFeB permanent magnet materials are widely used in wind power generation, new energy vehicles, industrial motors and other fields due to their high magnetic energy product. However, due to the low Curie temperature and high temperature coefficient of NdFeB magnets, they have poor thermal stability, which limits their application at high temperatures.

[0003] The temperature resistance of NdFeB magnets can be improved in two ways: one is to increase its Curie temperature, and the other is to reduce its temperature coefficient. For example, the invention patent CN111696743A discloses a method for preparing high-temperature resistant NdFeB magnets, which includes mixing ferroferric oxide powder and some chemical solvents in NdFeB powder, grinding the mixed powder to a particle size of 0.1~1 micron, and orienting and molding it in a 0.8~3.5T magnetic field and 500-800MPa pressure. Finally, it is cured at 120~180℃ for 1~3h to obtain a high-temperature resistant magnet of 320℃. However, the magnetic properties of the magnets prepared by this method are greatly damaged, and the magnetic energy product can only reach 15.2 kJ / m 3 . For example, the invention patent CN111554500 A prepares a high-temperature sintered NdFeB permanent magnet by vacuum mixing RM auxiliary alloy powder (R refers to one or more of Sm, Nd, Pr, and M refers to one or more of Cu, Al, Ni, Zn, and Nb) with NdFeB magnetic powder, and heating it to 550~750℃ for secondary mixing, and then forming, isostatic pressing, sintering and tempering. The absolute value of the remanence temperature coefficient of the magnet reaches 0.109~0.114% / K, and the absolute value of the coercive force temperature coefficient reaches 0.518~0.538% / K. However, this method has limited improvement on the temperature resistance of NdFeB magnets, and introduces the expensive Sm element, which increases the production cost of high-temperature NdFeB magnets. Therefore, it is particularly necessary to develop new high-temperature stability rare earth permanent magnet materials and preparation methods thereof.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The first object of the present invention is to provide a rare earth permanent magnet material with high temperature stability in view of one of the deficiencies of the current technology, which has good temperature stability and good magnetic properties.

[0006] The second object of the present invention is to provide a method for preparing a rare earth permanent magnetic material with high temperature stability, which is not limited by product specifications and has low cost.

[0007] The first object of the present invention is achieved by the following technical solution: A high temperature stability rare earth permanent magnet material, calculated by weight percentage, comprises the following chemical components: RE x Y y T z Tm a B b , wherein RE is at least one rare earth element selected from La, Ce, Pr, Nd, Gd, Tb, Dy, and Ho, x is 26 to 30, Y is yttrium, y is 0.5 to 5, and x+y is 29.8 to 34; Tm is at least one element selected from Al, Cu, Ga, Zr, Ti, and Si, a is 0.5 to 3; B is boron, b is 0.85 to 1.1; T is a combination of Fe and Co, z=100-xyab, and z contains 1 to 10 parts of Co; the microstructure of the high temperature stability rare earth permanent magnet material includes a main phase and a grain boundary phase, wherein the main phase accounts for about 88 to 94% and the grain boundary phase accounts for about 6 to 12%; the main phase is RE2(Fe, Co) 14 B structure, RE is at least one rare earth element selected from La, Ce, Pr, Nd, Gd, Tb, Dy, Ho, the main phase grain size is 2-8 μm, the Y concentration in the main phase is high in the grain center and low at the boundary; the grain boundary phase is a rare earth-rich phase, and RE is 1.2~ 2.5 FeM 0.2~0.38 The composition represents that RE is at least one rare earth element selected from La, Ce, Pr, Nd, Gd, Tb, Dy, and Ho, and M is an element selected from Al, Cu, Ga, Co, Zr, Ti, Y, and Si.

[0008] Through the above technical scheme, a suitable raw material ratio is selected, and by adding high-abundance rare earth element Y, the distribution of Y element in the main phase grains and grain boundary phases is regulated, thereby improving the microstructure of the main phase grains and grain boundary phases, thereby enhancing the de-exchange coupling effect of the magnet, thereby improving the high temperature stability of the magnet while maintaining the magnetic properties of the magnet.

[0009] Furthermore, the content ratio of the Y element in the grain core, grain boundary and grain boundary phase in the permanent magnet material is (0.5-5): (0.2-3): (0.1-1). The Y element has a high content in the grain core and a low content in the grain boundary and grain boundary phase, which meets the performance requirements.

[0010] Furthermore, the distribution ratio of the Y element in the permanent magnet material at the core of the main phase grains, the grain boundaries and the grain boundaries is (1.26~3.19): (0.78~1.58): (0.36~0.58).

[0011] Furthermore, the density of the permanent magnetic material is 7.2-7.5 g / cm3 The theoretical density of this permanent magnetic material is 7.6 g / cm 3 Therefore, the density of the final magnet is between 94.7% and 98.7%. Therefore, as long as the density is above 94.7%, the requirement can be met. Therefore, the preparation conditions are not very demanding, which is conducive to large-scale production.

[0012] Furthermore, the absolute value of the remanence temperature coefficient of the permanent magnet material is 0.06-0.1% / K at 20-120°C, and the absolute value of the coercivity temperature coefficient is 0.4-0.6% / K at 20-120°C. The final absolute values ​​of the remanence temperature coefficient and the coercivity temperature coefficient are both small, which greatly improves the temperature stability of the NdFeB magnet.

[0013] The second object of the present invention is achieved by the following scheme: A method for preparing a rare earth permanent magnet material with high temperature stability, comprising the following steps: rapidly casting and cooling an alloy ingot to obtain an alloy casting sheet with a thickness of 0.15-0.45 mm; the obtained alloy casting sheet is subjected to hydrogen absorption and dehydrogenation treatment in a hydrogen crushing furnace to obtain a coarse powder; the obtained coarse powder is uniformly mixed with an antioxidant and a lubricant, and then subjected to air flow grinding and secondary powder mixing to obtain a fine powder with a particle size of 2.7-3.1 μm; the obtained fine powder is oriented and formed by a magnetic field press, and then subjected to cold isostatic pressing to obtain a density of 3.9-4.1 g / cm 3 The green body is placed in a vacuum sintering furnace and vacuumed to 1×10 -2 Below Pa, gradient temperature rise sintering is performed; the blank after high temperature sintering is placed in a vacuum sintering furnace, and two-stage aging heat treatment is performed to obtain a rare earth permanent magnet material with high temperature stability.

[0014] Furthermore, the ingot is obtained by weighing RE element, Y element, T element, Tm element and ferroboron according to the chemical composition and mass percentage of the rare earth permanent magnet material, placing the weighed metal blocks in a vacuum melting furnace in a certain order, and rapidly heating and refining. The vacuum melting temperature is 1460~1490℃.

[0015] Furthermore, the casting temperature is 1450~1480℃.

[0016] Furthermore, the gradient temperature rise sintering is: firstly, the temperature is raised to 200-400°C for sintering for 0.5-2 hours, then the temperature is raised to 500-600°C for sintering for 0.5-3 hours, then the temperature is raised to 800-900°C for sintering for 0.5-3 hours, then the temperature is raised to 1050-1100°C for sintering for 8-12 hours, and finally the furnace is cooled to room temperature.

[0017] Furthermore, the two-stage aging heat treatment is as follows: heating to 850-950°C, keeping warm for 2-4 hours, cooling to room temperature with the furnace, then heating to 500-630°C, keeping warm for 3-5 hours, and cooling to room temperature with the furnace.

[0018] Compared with the prior art, the present invention has the following advantages:

[0019] The rare earth permanent magnet material of the present invention improves the temperature stability of the magnet by optimizing the formula design, reasonably adding the Y element, and combining the oxygen-free and heat treatment processes, so that the absolute value of the temperature coefficient of the magnet remanence is 0.06-0.1% / K, the absolute value of the temperature coefficient of the coercive force is 0.4-0.6% / K, and the temperature stability is high. The preparation method of the present invention adopts a vacuum melting temperature of 1460-1490°C and a casting temperature of 1450-1480°C, so that the high melting point Y2Fe 14 The B phase preferentially nucleates, and the Y element is enriched in the grains, which is conducive to the formation of a core-shell structure with different anisotropy fields. The Y element content in the core of the grain is high, and the Y element content in the grain boundary is low. The final magnet has high temperature stability and good magnetic properties. The preparation method of the present invention is all experimental steps used in the traditional magnet preparation method, is not limited by product specifications, and has low cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The following are the SEM electron microscope photos of the magnet in Example 3 and the corresponding SEM Mapping photos. Figure 1 (a) is a SEM microstructure photograph. Figure 1 (b) is Figure 1 The distribution of Fe in the area (a) is shown in the figure. Figure 1 (c) Figure 1 The distribution of Co in the (a) area. Figure 1 (d) is Figure 1 Photo of the Y element distribution in the middle (a) area;

[0021] Figure 2 The SEM micro-region morphology and corresponding composition diagram of the magnet in Example 3. DETAILED DESCRIPTION

[0022] The terms used herein are only for describing specific embodiments and are not intended to limit the present invention. Unless the context otherwise clearly indicates the opposite, the singular form used herein is also intended to include the plural form. It should also be understood that the term "comprising" does not specifically refer to a certain characteristic, field, integer, step, action, element and / or component, but excludes the existence or addition of other characteristics, fields, integers, steps, actions, elements, components and / or groups.

[0023] If a part is described as being "on" another part, it may be directly on the other part or there may be other parts therebetween. When a part is described as being "directly on" another part, there may be no other parts therebetween.

[0024] Although not otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as those commonly understood by those skilled in the art. Terms with definitions in dictionaries should be interpreted as having the same meaning as those disclosed in the relevant technical literature and this article, and should not be interpreted in an idealized or overly formal sense.

[0025] The contents of the present invention are described in detail below.

[0026] In a preferred example of the present invention, a method for preparing a rare earth permanent magnetic material with high temperature stability comprises the following steps:

[0027] Step 1: Raw material preparation: weigh RE element, Y element, T element, Tm element and ferroboron according to the chemical composition and mass percentage of the rare earth permanent magnet material;

[0028] Step 2: Vacuum melting, placing the weighed metal blocks in a vacuum melting furnace in a certain order, rapidly heating and refining, and then rapidly casting and cooling to obtain alloy castings;

[0029] Step 3: Hydrogen crushing: the alloy flakes obtained in step 2 are subjected to hydrogen absorption and dehydrogenation treatment in a hydrogen crushing furnace to obtain coarse powder;

[0030] Step 4: air flow milling, under the protection of inert gas, the coarse powder obtained in step 3 is mixed with an antioxidant and a lubricant, and then air flow milling and secondary powder mixing are performed to obtain fine powder;

[0031] Step 5: Orientation molding: The fine powder obtained in step 4 is oriented and molded by a magnetic field press, and then cold isostatic pressing is performed to obtain a density of 3.9~4.1g / cm 3 of greenware;

[0032] Step 6: Sintering: Place the green body obtained after step 5 into a vacuum sintering furnace and evacuate to 1×10 -2 Below Pa, gradient temperature rise sintering;

[0033] Step 7: Tempering: placing the high-temperature sintered blank in a vacuum sintering furnace and performing two-stage aging heat treatment to obtain a rare earth permanent magnet material with high temperature stability.

[0034] Furthermore, the vacuum melting temperature in step 2 is 1460-1490°C, and the casting temperature is 1450-1480°C.

[0035] Furthermore, the thickness of the alloy casting obtained in step 2 is 0.15-0.45 mm, and the temperature condition of dehydrogenation in step 3 is 420-480°C.

[0036] Furthermore, the particle size of the fine powder obtained in step 4 is 2.7-3.1 μm, the orientation pressing magnetic field of the orientation molding in step 5 is 1.8-2 T, the pressure of the cold isostatic pressing process is 180-210 MPa, and the pressure is maintained for 20-30 s.

[0037] Furthermore, the gradient temperature sintering in step six is: first, the temperature is increased to 200-400°C and sintered for 0.5-2 hours, then the temperature is increased to 500-600°C and sintered for 0.5-3 hours, then the temperature is increased to 800-900°C and sintered for 0.5-3 hours, then the temperature is increased to 1050-1100°C and sintered for 8-12 hours, and finally the furnace is cooled to room temperature.

[0038] Furthermore, the two-stage aging heat treatment of tempering in step seven is: heating to 850-950°C, keeping warm for 2-4 hours, cooling to room temperature with the furnace, then heating to 500-630°C, keeping warm for 3-5 hours, and cooling to room temperature with the furnace.

[0039] The high temperature stability rare earth permanent magnet material comprises the following chemical components by weight percentage: RE x Y y T z Tm a B b , wherein RE is at least one rare earth element selected from La, Ce, Pr, Nd, Gd, Tb, Dy, and Ho, x is 26 to 30, Y is yttrium, y is 0.5 to 5, and x+y is 29.8 to 34; Tm is at least one element selected from Al, Cu, Ga, Zr, Ti, and Si, a is 0.5 to 3; B is boron, b is 0.85 to 1.1; T is a combination of Fe and Co, z=100-xyab, and z contains 1 to 10 parts of Co; the microstructure of the high temperature stability rare earth permanent magnet material includes a main phase and a grain boundary phase, wherein the main phase accounts for about 88 to 94% and the grain boundary phase accounts for about 6 to 12%; the main phase is RE2(Fe, Co) 14 B structure, RE is at least one rare earth element selected from La, Ce, Pr, Nd, Gd, Tb, Dy, Ho, the main phase grain size is 2-8 μm, the Y concentration in the main phase is high in the grain center and low at the boundary; the grain boundary phase is a rare earth-rich phase, and RE is 1.2~2.5 FeM 0.2~0.38 The composition represents that RE is at least one rare earth element selected from La, Ce, Pr, Nd, Gd, Tb, Dy, and Ho, and M is an element selected from Al, Cu, Ga, Co, Zr, Ti, Y, and Si.

[0040] The rare earth permanent magnet material with high temperature stability and high magnetic performance and its preparation method of the present invention are described below in conjunction with the accompanying drawings and embodiments. However, the present invention can be implemented in various different ways and is not limited to the embodiments described herein.

[0041] Example 1

[0042] According to the following chemical composition and mass percentage: PrNd: 29wt%, Y: 1%, Ti: 0.18wt%, Al: 0.1wt%, Ga: 0.2wt%, Co: 0.5wt%, Cu: 0.4wt%, B: 0.92wt%, and the balance is Fe, PrNd, Y, Ti, Al, Cu, Ga, Co, ferroboron and pure iron are weighed; the weighed metal blocks are placed in a vacuum melting furnace in the order of iron, titanium, ferroboron, yttrium, cobalt, copper, aluminum and gallium, melted at 1478°C, and cast at 1462°C to obtain 0.25-0.35mm NdFeB magnet alloy castings.

[0043] The NdFeB magnet alloy casting sheet is subjected to hydrogen absorption treatment and dehydrogenation treatment at 450°C to obtain a coarse powder. Antioxidants and lubricants, namely 0.8 g / kg of 3# agent, 0.425 g / kg of Yang-yang agent, and 1.2 g / kg of gasoline are added to the coarse powder; under the protection of inert gas, the powder is ground into a fine NdFeB powder with a particle size of 2.82 μm.

[0044] Fine powder (0.425 g / kg of sun-adjusting agent was added to the fine powder) was oriented and formed in a 2T magnetic field using a magnetic field press, and isostatically pressed at 190 MPa for 20 s to obtain a density of 4.05 g / cm 3 The L50mm×30mm×40mm square green body has its orientation direction in the 40mm direction.

[0045] The NdFeB green body is placed in a vacuum sintering furnace and the vacuum is evacuated to 1×10 -2 Pa, first heat to 260℃ and sinter for 0.5 hours, then heat to 380℃ and sinter for 1.5 hours, then heat to 600℃ and 800℃ and sinter for 2 hours respectively, then heat to 900℃ and sinter for 1 hour, then heat to 1060℃ and sinter for 10 hours, and finally cool to room temperature with the furnace. Then, place the blank after high-temperature sintering in a vacuum sintering furnace for aging in two stages, first heat to 900℃, keep warm for 3 hours, cool to room temperature with the furnace, then heat to 620℃, keep warm for 4 hours, and cool to room temperature with the furnace to obtain a high temperature resistant NdFeB magnet.

[0046] Example 2

[0047] The NdFeB magnets were sintered according to the chemical composition and preparation method of the NdFeB magnets in Example 1, except that the mass percentage of Y was 2%, and the mass percentages of other elements remained unchanged; the melting temperature was 1485°C, the casting temperature was 1466°C, and other processes remained unchanged.

[0048] Example 3

[0049] The NdFeB magnets were sintered according to the chemical composition, mass percentage and preparation method of the NdFeB magnets in Example 1, except that the mass percentage of Y was 3% and the mass percentages of other elements remained unchanged; the melting temperature was 1486°C, the casting temperature was 1465°C, and other processes remained unchanged.

[0050] Comparative Example 1

[0051] According to the following chemical composition and mass percentage: PrNd: 29wt%, Ti: 0.18wt%, Al: 0.1wt%, Ga: 0.2wt%, Co: 0.5wt%, Cu: 0.4wt%, B: 0.92wt%, and the balance is Fe, a sintered NdFeB magnet was prepared according to the preparation method described in Example 1, except that the melting temperature was 1468°C, the casting temperature was 1456°C, and the other processes remained unchanged.

[0052] Comparative Example 2

[0053] The NdFeB magnets were sintered according to the chemical composition, mass percentage and preparation method of the NdFeB magnets in Example 1, except that the maximum temperature during the sintering process in step six was 1070° C. and the temperature was kept for 10 hours.

[0054] Comparative Example 3

[0055] The NdFeB magnets were sintered according to the chemical composition, mass percentage and preparation method of the NdFeB magnets in Example 1, except that the maximum temperature during the sintering process in step six was 1050° C. and the temperature was kept for 10 hours.

[0056] The magnets obtained in Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2 and Comparative Example 3 were prepared into samples of φ10 mm×10 mm by wire cutting, wherein the axial direction was the orientation direction, and magnetic properties were tested using a BH analyzer. The obtained magnetic properties and temperature stability are shown in Table 1. The temperature range of the temperature stability test is 20-120°C. The actual maximum use temperature of the magnet is greater than 120°C.

[0057] Table 1 Magnetic properties and temperature stability of sintered NdFeB magnets

[0058]

[0059] It can be seen from the data in Table 1 that the remanence of comparative example 1 is the highest, but the coercive force is only 13.71 kOe, and the temperature stability is the worst; the remanence of embodiments 2 and 3 is lower, but their temperature resistance is better than that of comparative examples 1, 2 and 3; the remanence temperature coefficient of embodiment 1 is only -0.089% / K, and the coercive force temperature coefficient is only -0.558% / K. Embodiment 1 has the best temperature resistance and has good magnetic properties, which can simultaneously meet the requirements of the magnet for magnetic properties and temperature resistance.

[0060] The microstructure of the magnet of Example 3 was analyzed by scanning electron microscopy. Figure 1 The distribution of the Y element in the magnet of Example 3 is also analyzed, as shown in the gray figure in (a). Figure 1 The distribution statistics of Y element in the sintered NdFeB permanent magnets of Examples 1-3 are shown in Table 2.

[0061] Table 2 Statistical values ​​of Y element distribution in sintered NdFeB permanent magnets

[0062]

[0063] From the data in Table 2, it can be seen that the concentration of Y element shows a trend of gradually decreasing from the core of the matrix phase to the grain boundary and then to the grain boundary phase. Figure 2 , Figure 2 The left picture is the actual SEM microstructure diagram, in which the grains and grain boundaries are pointed out. Figure 2 The right side of the figure is based on the left side and combined with Figure 1 Schematic diagram of the Y element distribution given by the composition analysis. The darker the color, the higher the Y content.

[0064] Example 4

[0065] According to the following chemical composition and mass percentage: PrNd: 30.5wt%, Y: 2%, Ti: 0.18wt%, Al: 0.1wt%, Ga: 0.2wt%, Co: 2wt%, Cu: 0.4wt%, B: 0.92wt%, and the balance is Fe, PrNd, Y, Ti, Al, Cu, Ga, Co, ferroboron and pure iron are weighed; the weighed metal blocks are placed in a vacuum melting furnace in the order of iron, titanium, ferroboron, yttrium, cobalt, copper, aluminum and gallium, the vacuum melting temperature is 1485°C, the casting temperature is 1468°C, and the NdFeB magnet alloy casting sheet of 0.25-0.35mm is obtained by melting.

[0066] The NdFeB magnet alloy casting sheet is subjected to hydrogen absorption treatment and dehydrogenation treatment at 450° C. to obtain a coarse powder. An antioxidant and a lubricant are added to the coarse powder, and the powder is ground into a NdFeB fine powder with a particle size of 2.81 μm under the protection of an inert gas.

[0067] The fine powder was oriented and molded in a 2T magnetic field using a magnetic field press and isostatically pressed at 190 MPa for 20 s to obtain a density of 4.05 g / cm 3 The L50mm×30mm×40mm square green body has its orientation direction in the 40mm direction.

[0068] The NdFeB green body is placed in a vacuum sintering furnace and the vacuum is evacuated to 1×10 -2 Pa, firstly, the temperature is raised to 260℃ and sintered for 0.5 hours, then raised to 380℃ and sintered for 1.5 hours, then raised to 600℃ and 800℃ and sintered for 2 hours respectively, then raised to 900℃ and sintered for 1 hour, then raised to 1055℃ and sintered for 10 hours, and finally cooled to room temperature with the furnace. Then, the green body after high temperature sintering is placed in a vacuum sintering furnace, and aged in two stages, raised to 900℃, kept warm for 3 hours, cooled to room temperature with the furnace, then raised to 600℃, kept warm for 4 hours, cooled to room temperature with the furnace, and then a high temperature resistant NdFeB magnet can be obtained. The magnetic properties of the magnet are tested, and the results show that Br is 13.85 kGs, Hcj is 15.63kOe, the remanence temperature coefficient is -0.095% / K, and the coercivity temperature coefficient is -0.571% / K.

[0069] Example 5

[0070] According to the following chemical composition and mass percentage: PrNd: 32.1wt%, Y: 2%, Ti: 0.18wt%, Al: 0.1wt%, Ga: 0.4wt%, Co: 1wt%, Cu: 0.5wt%, B: 0.91wt%, and the balance is Fe, PrNd, Y, Ti, Al, Cu, Ga, Co, ferroboron and pure iron are weighed; the weighed metal blocks are placed in a vacuum melting furnace in the order of iron, titanium, ferroboron, yttrium, cobalt, copper, aluminum and gallium. The vacuum melting temperature is 1488°C, the casting temperature is 1468°C, and the NdFeB magnet alloy casting sheet with a diameter of 0.25-0.35mm is obtained by melting.

[0071] The NdFeB magnet alloy casting sheet is subjected to hydrogen absorption treatment and dehydrogenation treatment at 450° C. to obtain a coarse powder. An antioxidant and a lubricant are added to the coarse powder, and the powder is ground into a NdFeB fine powder with a particle size of 2.85 μm under the protection of an inert gas.

[0072] The fine powder was oriented and molded in a 2T magnetic field using a magnetic field press and isostatically pressed at 190 MPa for 20 s to obtain a density of 4.05 g / cm 3 The L50mm×30mm×40mm square green body has its orientation direction in the 40mm direction.

[0073] The NdFeB green body is placed in a vacuum sintering furnace and the vacuum is evacuated to 1×10 -2 Pa, firstly, the temperature is raised to 260℃ and sintered for 0.5 hours, then raised to 380℃ and sintered for 1.5 hours, then raised to 600℃ and 800℃ and sintered for 2 hours respectively, then raised to 900℃ and sintered for 1 hour, then raised to 1050℃ and sintered for 8 hours, and finally cooled to room temperature with the furnace. Then, the green body after high temperature sintering is placed in a vacuum sintering furnace, and aged in two stages, raised to 900℃, kept warm for 3 hours, cooled to room temperature with the furnace, then raised to 550℃, kept warm for 4 hours, cooled to room temperature with the furnace, and then a high temperature resistant NdFeB magnet can be obtained. The magnetic properties of the magnet were tested, and the results showed that Br was 13.56 kGs, Hcj was 18.36kOe, the remanence temperature coefficient was -0.087% / K, and the coercivity temperature coefficient was -0.552% / K.

[0074] In summary, the present invention promotes the formation of the core-shell structure of the magnet by optimizing the formula design, reasonably adding the Y element, and combining the oxygen-free and heat treatment process improvements. While meeting the magnetic properties, the temperature stability of the NdFeB magnet is greatly improved.

[0075] The present invention can be implemented in various ways and is not limited to the above-mentioned embodiments and / or examples. A person skilled in the art can understand that the present invention can be implemented in other specific ways without changing the technical concept or essential features of the present invention. Therefore, it should be understood that the above-mentioned embodiments and / or examples are exemplary and are not intended to limit the present invention.

Claims

1. A rare earth permanent magnetic material with high temperature stability, characterized in that: By weight percentage, it includes the following chemical components: RE x Y y T z Tm a B b , wherein RE is at least one rare earth element selected from La, Ce, Pr, Nd, Gd, Tb, Dy, and Ho, x is 26 to 30, Y is yttrium, y is 0.5 to 5, and x+y is 29.8 to 34; Tm is at least one element selected from Al, Cu, Ga, Zr, Ti, and Si, a is 0.5 to 3; B is boron, b is 0.85 to 1.1; T is an element combination of Fe and Co, z=100-xyab, and the content of Co is 0.5 wt% or 1 wt% or 2 wt% of the high temperature stability rare earth permanent magnet material; The microstructure of the high temperature stability rare earth permanent magnet material includes a main phase and a grain boundary phase, wherein the main phase accounts for 88-94% and the grain boundary phase accounts for 6-12%; the main phase is RE2 (Fe, Co) 14 B structure, RE is at least one rare earth element selected from La, Ce, Pr, Nd, Gd, Tb, Dy, Ho, the main phase grain size is 2-8 μm, the Y concentration in the main phase is high in the grain center and low at the boundary; the grain boundary phase is a rare earth-rich phase, and RE is 1.2~2.5 FeM 0.2~0.38 The composition represents that RE is at least one rare earth element selected from La, Ce, Pr, Nd, Gd, Tb, Dy, and Ho, and M is an element selected from Al, Cu, Ga, Co, Zr, Ti, Y, and Si.

2. The high temperature stability rare earth permanent magnetic material according to claim 1, characterized in that: The content ratio of the Y element in the permanent magnetic material in the grain core, grain boundary and grain boundary phase is (0.5-5): (0.2-3): (0.1-1).

3. The high temperature stability rare earth permanent magnetic material according to claim 2, characterized in that: The distribution ratio of the Y element in the permanent magnet material at the core of the main phase grains, the grain boundaries and the grain boundaries is (1.26-3.19): (0.78-1.58): (0.36-0.58).

4. The high temperature stability rare earth permanent magnetic material according to claim 1, characterized in that: The density of the permanent magnetic material is 7.2-7.5 g / cm 3 .

5. The high temperature stability rare earth permanent magnetic material according to claim 1, characterized in that: The absolute value of the remanence temperature coefficient of the permanent magnetic material is 0.06-0.1% / K at 20-120°C, and the absolute value of the coercive force temperature coefficient is 0.4-0.6% / K at 20-120°C.

6. The method for preparing the high temperature stability rare earth permanent magnetic material according to any one of claims 1 to 5, characterized in that: The following steps are involved: The alloy ingot is rapidly cast and cooled to obtain an alloy casting sheet with a thickness of 0.15-0.45 mm; the alloy casting sheet is subjected to hydrogen absorption and dehydrogenation treatment in a hydrogen crushing furnace to obtain a coarse powder; the coarse powder is uniformly mixed with an antioxidant and a lubricant, and then subjected to air flow grinding and secondary powder mixing to obtain a fine powder with a particle size of 2.7-3.1 μm; the fine powder is oriented and formed by a magnetic field press, and then subjected to cold isostatic pressing to obtain a density of 3.9-4.1 g / cm 3 The green body is placed in a vacuum sintering furnace and vacuumed to 1×10 -2 Below Pa, gradient temperature rise sintering is performed; the blank after high temperature sintering is placed in a vacuum sintering furnace, and two-stage aging heat treatment is performed to obtain a rare earth permanent magnet material with high temperature stability.

7. The preparation method according to claim 6, characterized in that: The ingot is obtained by weighing RE element, Y element, T element, Tm element and ferroboron according to the chemical composition and mass percentage of the rare earth permanent magnet material, placing the weighed metal blocks in a vacuum melting furnace in a certain order, and rapidly heating and refining. The vacuum melting temperature is 1460-1490°C.

8. The preparation method according to claim 6, characterized in that: The casting temperature is 1450~1480℃.

9. The preparation method according to claim 6, characterized in that: The gradient temperature sintering is as follows: firstly, the temperature is raised to 200-400°C for sintering for 0.5-2 hours, then the temperature is raised to 500-600°C for sintering for 0.5-3 hours, then the temperature is raised to 800-900°C for sintering for 0.5-3 hours, then the temperature is raised to 1050-1100°C for sintering for 8-12 hours, and finally the furnace is cooled to room temperature.

10. The preparation method according to claim 6, characterized in that: The two-stage aging heat treatment is as follows: heating to 850-950°C, keeping the temperature for 2-4 hours, cooling to room temperature with the furnace, then heating to 500-630°C, keeping the temperature for 3-5 hours, and cooling to room temperature with the furnace.

Citation Information

Cited By

  • Doping preparation method of high-temperature stable rare earth magnet assembly

    CN121964372A